DIFFICULTIES WHICH ARE FACED BY FOREIGN LANGUAGE LEARNERS - Xoliqova Xumora Jahongir qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This article examines the challenges faced by learners of foreign languages. In today's world, knowing multiple languages is increasingly important. Learning a foreign language is a demanding task, requiring significant effort to navigate complex linguistic structures and learn to think in a new way. While challenging, the rewards of language acquisition are substantial, including enhanced communication skills, cultural understanding, and career opportunities.